Noise Test and Optimization of Auxiliary Converter for Metro Vehicle - DING Jie; HE Yanfei; ZENG Yaping; DENG Chuanghua (机车电传动)
In order to reduce the noise of auxiliary converter in metro vehicle, noise characteristics of the auxiliary converter were obtained through the vibration and noise test in different working conditions. Based above, the noise transfer path analysis, optimization of duct structure, and duct muffler treatment were carried out. With the results, it was shown that noise of the fan at full load and high speed was the highest, and the noise in idle condition and low speed was smaller. The noise below 1 250 Hz was mainly the aerodynamic noise of the fan. In the range of 1 250 Hz~10 kHz, mechanical noise and electromagnetic noise contributed the most. Many main peak frequencies of vibrations were basically consistent with those of the noise, correlation between vibration and noise was significant. At high-speed and full load, the noise values of the measured points in the fan reduced 8.6~12.2 dB (A) after optimization, which indicated that the noise reduction effect was significant.